Effect of Learning Search, Solve, Create and Share with Metacognitive Strategies to Solving Ability and Critical Thinking Physics - Nia Suciati (Jurnal Pendidikan Sains, 2013)
Pengaruh Pembelajaran Search, Solve, Create dan Share dengan Strategi Metakognitif terhadap Kemampuan Menyelesaikan Masalah dan Berpikir Kritis Fisika Abstract: This study aims to examine the differences in students 'abilities to think critically and solve problems of physics and the effectiveness of the learning model SSCS with metacognitive strategies to improve students' skills in problem solving and critical thinking physics compared with SSCS learning model and conventional learning. The design of the study is postest Only Control Group Design with a random sample selection. Data were collected through tests problem solving skills, critical thinking skills tests, and observation of learning. The results showed that there are differences in students 'abilities to think critically and solve problems of physics and SSCS learning model with a more effective metacognitive strategies to improve students' skills in critical thinking to solve the problem of physics than the SSCS learning model and conventional learning. Key Words: SSCS learning, metacognitive strategies, solve problems, think critically Abstrak: Penelitian ini bertujuan menguji perbedaan kemampuan siswa menyelesaikan masalah dan berpikir kritis fisika serta efektifitas model pembelajaran SSCS dengan strategi metakognitif untuk meningkatkan kemampuan siswa dalam menyelesaikan masalah dan berpikir kritis fisika dibandingkan dengan model pembelajaran SSCS dan pembelajaran konvensional. Rancangan penelitian yang digunakan adalah Postest Only Control Group Design dengan pemilihan sampel acak. Data dikumpulkan melalui tes kemampuan menyelesaikan masalah, tes kemampuan berpikir kritis, dan observasi pembelajaran. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan siswa menyelesaikan masalah dan berpikir kritis fisika serta model pembelajaran SSCS dengan strategi metakognitif lebih efektif untuk meningkatkan kemampuan siswa dalam menyelesaikan masalah berpikir kritis fisika dibandingkan dengan model pembelajaran SSCS dan pembelajaran konvensional.Kata kunci: pembelajaran SSCS, strategi metakognitif, menyelesaikan masalah, berpikir kritis